2000
DOI: 10.1046/j.1365-201x.2000.00738.x
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide prevents rat duodenal contractions induced by potentially noxious agents

Abstract: After abdominal surgery, luminal HCl fails to induce duodenal contractions in anaesthetized rats. Elevated tissue levels of nitric oxide (NO) and prostaglandins possibly contribute to this observation. The aim of this study was to compare the effects of luminal capsaicin (1.2 mg mL-1), ethanol (15%) and high partial pressure of CO2 (>250 mmHg) with those of HCl (10 mM) in anaesthetized rats. Motility (intraluminal pressure), mucosal permeability [blood-to-lumen clearance of 51Cr-EDTA (51Chromium-labelled ethyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…It also decrease in adipose tissue mass has a role to play in weight management. In addition, capsaicin affects various physiological functions which include intestinal peristalsis (Hellgren et al, 2000), gastroprotection (Szoscanyi and Bartho, 2001), temperature regulation (Nomoto et al, 2004), modulation of the energy metabolism (Kawada et al, 1986), immune status (Yu et al, 1998) and blood neuthrophils (Zhukova and Makarova, 2002). Capsaicin has also been found to exert protective effect against Salmonela enteritidis infection in laying hens (Vicente et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…It also decrease in adipose tissue mass has a role to play in weight management. In addition, capsaicin affects various physiological functions which include intestinal peristalsis (Hellgren et al, 2000), gastroprotection (Szoscanyi and Bartho, 2001), temperature regulation (Nomoto et al, 2004), modulation of the energy metabolism (Kawada et al, 1986), immune status (Yu et al, 1998) and blood neuthrophils (Zhukova and Makarova, 2002). Capsaicin has also been found to exert protective effect against Salmonela enteritidis infection in laying hens (Vicente et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…However, relatively little is known about the involvement of intramural neurohumoral regulation of the intestinal permeability in the intact animal. Recent experiments from our laboratory have shown that luminal perfusion of the rat duodenum with various solutions such as hydrochloric acid , ethanol and hypo‐ and hyperosmolar fluids affects the blood‐to‐lumen clearance of 51 Cr‐EDTA, a reliable technique to assess changes in epithelial paracellular permeability. It was further demonstrated that the hypotonicity‐induced increases in duodenal paracellular permeability are mediated via serotonin (5‐HT) acting on 5‐HT 3 and 5‐HT 4 receptors as well as by changes in neural activity possibly suggesting that the enteric nervous system participates in the regulation of tight junction epithelial permeability.…”
Section: Introductionmentioning
confidence: 99%
“…Noxious agents have been shown to disrupt this barrier and increase the clearance of large molecules from blood to lumen (14,21). Different research groups have shown that inhibition of endogenous NO production leads to an increase in mucosal permeability (22,28). Several studies have also shown that nonsteroidal anti-inflammatory drugs (NSAIDs) increase the mucosal permeability (15).…”
mentioning
confidence: 99%